Pengaruh Tingkat Suku Bunga, Earning Per Share, Dan Book Value Per Share Terhadap Harga Saham Perusahaan Rokok Di IHSG - Kenneth Osbert; Ririt Iriani (CV. Ulil Albab Corp, 2022)
This article discusses the effect of combining the company's external factors in the form of interest rates and internal company factors as well as included in the financial statements, namely Earning Per Share (EPS) and Book Value Per Share (BVPS) which are used as free variables on the stock price of cigarette companies listed in the IHSG which are bound variables. This study was tested using a regression analysis of panel data from 4 cigarette companies listed in the IHSG during 2015-2019, namely PT Gudang Garam Tbk, PT HM Sampoerna Tbk, PT Wismilak Inti Makmur Tbk, and PT Bentoel Internasional Investama Tbk. From the results of this study, it shows that the presence of evidence that interest rates have a significant effect on the stock price of cigarette companies, in addition, interest rates negatively affect the stock price of cigarette companies. While EPS and BVPS have a positive and significant effect on the stock price of cigarette companies.